Rancang Bangun Sistem Smart Parkir Berbasis Arduino - Hendy Tri Laksono; Zuly Budiarso (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
Parking lots are of course the first thing to look for when we are in public places. However, conventional parking lots often do not provide adequate information about the slots that are still available in parking area. This research on a smart parking system consists of an Ultrasonic Hc-Sr04 sensor to know the parking slots that are occupied or empty. The information can be viewed on LCD screen on the entrance of parking lots, telling in details whether the parking slots are occupied or still available. Based on the Arduino Uno test results, the sensor can manage the circuit properly and display information about available parking slots. Besides that, the Ultrasonic Hc-Sr04 sensor can detect vehicles in the parking area and can set the front bar to prevent other vehicles from entering when the entire parking area is full.